Advancements and Regulatory Situation in Microplastics Removal from Wastewater and Drinking Water: A Comprehensive Review - Vyoma Jani; Shenghua Wu; Kaushik Venkiteshwaran (Microplastics, 2024)
In recent years, the ubiquitous occurrence of plastic debris has become a significant environmental concern, posing considerable harm to our ecosystems. Microplastics (MPs) (1 μm–5 mm) and nanoplastics (NPs) (<1 μm) are noticeable in diverse forms, spreading throughout the environment. Notably, wastewater treatment plants (WWTPs) emerge as major contributors to the generation of MP and NP. Within these treatment plants, water influx from domestic and commercial sources carries a considerable load of MPs derived from items like fiber clothing, personal care products, and toothpaste. Lacking dedicated removal mechanisms, these MPs persist through the wastewater treatment process, ultimately entering natural water bodies and the soil environment. The novelty of this review lies in its detailed examination of contemporary methodologies for sampling, detecting, and eliminating MPs specifically from WWTPs. By critically assessing the efficacy of current removal techniques at various treatment stages, the review offers targeted insights into practical aspects of MP management in these facilities. As the study of micro/nano plastics is still in its early stages, this article aims to contribute by offering a comprehensive review of the methods utilized for plastic debris removal in both WWTPs and drinking water treatment plants (DWTPs). Furthermore, the article provides a comprehensive overview of the existing rules, regulations, and policies concerning MPs in the United States. This inclusion not only broadens the scope of the review but also establishes it as a valuable reference for understanding the regulatory framework related to MPs. This review uniquely combines a focused evaluation of WWTPs/DWTPs, an exploration of removal methods, and an examination of regulatory framework, making a different contribution to the review article. Through this review, we aim to enhance understanding and awareness of the multi-layered challenges posed by MPs, offering insights that can inform future research directions and policy initiatives.